Narrow‐leafed lupin (Lupinus angustifolius L.) β‐conglutin proteins modulate the insulin signaling pathway as potential type 2 diabetes treatment and inflammatory‐related disease amelioration. Issue 5 (13th February 2017) - Lima‐Cabello, Elena; Alche, Victor; Foley, Rhonda C.; Andrikopoulos, Sofianos; Morahan, Grant; Singh, Karam B.; Alche, Juan D.; Jimenez‐Lopez, Jose C.
Abstract : This study provides new insights about the potential use of β‐conglutin seed proteins from the legume Lupinus angustifolius L. in the type 2 diabetes prevention and treatment, and as anti‐inflammatory molecules: (i) β1‐, β3‐, and β6‐conglutins have the ability to modulate the expression levels of crucial genes involved in the insulin molecular signaling pathway. (ii) The same conglutins trigger the release of the pro‐inflammatory capacity of cells by diminishing IL 1 beta and inducible nitric oxide synthase expression levels, leading to amelioration of the inflammatory process associated with type 2 diabetes. Abstract : Scope: We have investigated the potential use of β‐conglutin protein isoforms from narrow‐leafed lupin ( Lupinus angustifolius L.) as a diabetes treatment. Methods and results: We produced purified recombinant β1‐, β2‐, β3‐, β4‐, and β6‐conglutin proteins and showed that β1, β3, and β6 could bind to insulin. To assess β‐conglutin proteins modulatory effect on insulin activation meditated kinases, whole blood and peripheral blood mononuclear cell cultures from type 2 diabetes (T2D) and healthy control subjects (C) were incubated with conglutin proteins. The treatment of peripheral blood mononuclear cells from T2D patients with β1, β3, and β6 proteins increased up to threefold mRNA and protein levels of genes important in insulin signaling pathways, namely insulin receptor substrate 1/p85/AKT/glucose transporter type 4. This was accompanied by a comparable fold‐change decrease in the mRNA expression level of pro‐inflammatory genes ( iNOS and IL‐1β ) and proteins compared to healthy controls. The β2 and β4 isoforms had no effect on the insulin signaling pathway. However, these β‐conglutin proteins elicited pro‐inflammatory effects since levels of mRNA and proteins of inducible nitric oxide synthase and IL 1 beta were increased. Conclusion: Our results raise the possibility of using these particular β‐conglutin proteins in the prevention and treatment of diabetes, as well as their potential as anti‐inflammatory molecules.